Practical Application of Logic in Administrative Processes in the Field of Intellectual Property - Samaniego Izurieta, Luis Fernando (2017)
The document evaluates the application of logic in administrative processes in the field of intellectual property. Additionally, it establishes the main methods for the use of logic in intellectual property and formulates practical solutions that encompass the problems associated with the omission of logic and the benefits derived from them. KEY WORDS: legal logic, administrative processes, intellectual property, principles, methods. JEL CODE / CLASIFICACIÓN JEL: H53, H72